Jinping Neutrino Experiment: a Status Report. (February 2020) - Xu, Benda
Abstract: A large liquid scintillator detector is being discussed and actively developed in China JinPing underground Laboratory. We envision a 5kt detector at 7000-water-meter-equivalent overburden to target terrestrial, solar and supernovae neutrinos. A 1t prototype detector has been installed on-site in 2017. Liquid scintillator performance, radioactive and cosmogenic backgrounds, simulation and analysis pipelines have been carefully investigated. We report the status of the Jinping Neutrino Experiment project and milestones of R&D studies.